2016
DOI: 10.1080/17513758.2016.1143533
|View full text |Cite
|
Sign up to set email alerts
|

Modelling populations ofLygus hesperuson cotton fields in the San Joaquin Valley of California: the importance of statistical and mathematical model choice

Abstract: Understanding the population dynamics of herbivorous insects is critical to developing and implementing effective pest control protocols. In the context of inverse problems, we explore the dynamic effects of pesticide treatments on Lygus hesperus, a common pest of cotton in the western United States. Fitting models to field data, we explore the topic of model selection for an appropriate mathematical model and corresponding statistical models, and use techniques including ANOVA-based model comparison tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The data used came from a database consisting of approximately 1500 replicates of L. hesperus density counts, using sweep counts, in over 500 Pima or Acala cotton fields in 1997-2008 in the San Joaquin Valley of California. This data is described more fully in [2]. We selected subsets to analyze using the following criteria:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data used came from a database consisting of approximately 1500 replicates of L. hesperus density counts, using sweep counts, in over 500 Pima or Acala cotton fields in 1997-2008 in the San Joaquin Valley of California. This data is described more fully in [2]. We selected subsets to analyze using the following criteria:…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, this includes selection of both statistical and mathematical models in fits-to-data -something that is not always fully explicitly addressed in the ecological literature. We first addressed this gap in [1,2] using data from pest population counts of Lygus hesperus Knight (Hemiptera: Meridae) feeding on pesticide-treated cotton fields in the San Joaquin Valley of California [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiences [4,3,5,6] with other ecological and population modeling efforts involving population counts have suggested that some type of error process depending on the size of the population is likely to be most appropriate. This motivates our choice of statistical model in (2).…”
Section: Formulation Of the Inverse Problemmentioning
confidence: 99%